Molecular Characterization of a Dual Domain Carbonic Anhydrase From the Ctenidium of the Giant Clam, Tridacna squamosa, and Its Expression Levels After Light Exposure, Cellular Localization, and Possible Role in the Uptake of Exogenous Inorganic Carbon - Koh, Clarissa Z. Y.; Hiong, Kum C.; Choo, Celine Y. L.; Boo, Mel V.; Wong, Wai P.; Chew, Shit F.; Neo, Mei L.; Ip, Yuen K. (Frontiers in Physiology, 2018)
A Dual-Domain Carbonic Anhydrase (DDCA) had been sequenced and characterized from the ctenidia (gills) of the giant clam, Tridacna squamosa, which lives in symbiosis with zooxanthellae. DDCA was expressed predominantly in the ctenidium. The complete cDNA coding sequence of DDCA from T. squamosa comprised 1,803 bp, encoding a protein of 601 amino acids and 66.7 kDa. The deduced DDCA sequence contained two distinct α-CA domains, each with a specific catalytic site. It had a high sequence similarity with tgCA from Tridacna gigas. In T. squamosa, the DDCA was localized apically in certain epithelial cells near the base of the ctenidial filament and the epithelial cells surrounding the tertiary water channels. Due to the presence of two transmembrane regions in the DDCA, one of the Zn2+-containing active sites could be located externally and the other one inside the cell. These results denote that the ctenidial DDCA was positioned to dehydrate HCO3− to CO2 in seawater, and to hydrate the CO2 that had permeated the apical membrane back to HCO3− in the cytoplasm. During insolation, the host clam needs to increase the uptake of inorganic carbon from the ambient seawater to benefit the symbiotic zooxanthellae; only then, can the symbionts conduct photosynthesis and share the photosynthates with the host. Indeed, the transcript and protein levels of DDCA/DDCA in the ctenidium of T. squamosa increased significantly after 6 and 12 h of exposure to light, respectively, denoting that DDCA could participate in the light-enhanced uptake and assimilation of exogenous inorganic carbon.